In-situ electrodeposition of metal free poly-cysteine decorated graphitic carbon nitride for synchronous analysis of Zn+2 and Cd+2 - Kumar Singh A.; Tarul; Patel M.; Rosy (My University, 2025)
The increasing presence of heavy metal ions (HMIs) in the ecosystem poses a substantial risk to human health. It is crucial to carefully analyze the trace levels of HMIs like zinc and cadmium in water bodies, food items, and air. Herein, a single-step electrodeposition of poly(Cysteine).gCN is presented as a feasible surface modification strategy for the sensing of Zn+2 and Cd+2. The synergistic interaction of cysteine and gCN offered specific chemical affinity, larger active surface area, and electron-donor N-sites for the synchronous analysis of Zn+2 and Cd+2. The electrochemical studies reveal that the poly(Cysteine).gCN modified electrode exhibited electro-catalytic activity showcasing ∼9.5 times and 18 times higher current response for Zn+2 and Cd+2, respectively. The developed sensor demonstrated high sensitivity (0.03 µA/µM for Zn+2 and 0.12 µA/µM for Cd+2), wide response range (7.5–100 µM for Zn+2 and 1–100 µM for Cd+2), and lower limit of detection (18.60 nM for Zn+2 and 4.90 nM for Cd+2). Additionally, the sensor demonstrated an interference-free response in the presence of ten other metal ions. For application, the developed sensor was employed to detect Zn+2 and Cd+2 metal ions in various water samples. © 2025 Elsevier Ltd